Mechanical performance of granite fine fly dust-filled basalt/glass polyurethane polymer hybrid composites - Sapiai, Napisah; Jumahat, Aidah; Jawaid, Mohammad; Abu, Md Zin; Chalid, Mochamad (MDPI, 2021)
The granite processing industry generates large amounts of bottom granite dust waste every day. After the drying and heating process of concrete mixture production, the granite dust is blown and collected in the filtering nozzle. This very fine particle granite dry fly dust, with a particle size maximum distribution of 500 μm, can easily be blown away by wind and cause serious environmental impacts. The use of this waste material would be an effective way to reduce such impacts. Therefore, this paper presents an experimental study on the potential of granite dust as a filler in enhancing the mechanical performance of a hybrid basalt/glass (WB/GCSM) composite. The unhole and open hole tensile (UHT and OHT) properties, low velocity impact (LVI) properties, quasi-static indentations (QSI) properties, flexural properties, interlaminar shear stress (ILSS) properties, and morphology of the developed WB/GCSM composites were evaluated. To meet the objective of this study, composite specimens were produced using 1.5–60 μm granite fly dust at three (3) different loadings (1, 3 and 5 wt%). This granite fly dust was incorporated into polyurethane resin using a mechanical stirring technique. The production of FRP laminates then completed using a hand lay-up and vacuum bagging technique. Four types of the WB/GCSM composites systems, i.e., [WB/GCSM], [WB/GCSM/1GD], [WB/GCSM/3GD] and [WB/GCSM/5GD] were fabricated and compared. The analysis results for the mechanical tests revealed that the incorporation of granite dust of up to 3 wt% had increased the UHT, OHT, LVI, QSI, flexural and ILSS properties of all WB/GCSM composites systems. Higher levels of damage tolerance in UHT and OHT tests, and increased ductility index in the LVI test were obtained when granite dust was added up to 5 wt%. However, a remarkable improvement in all mechanical properties was noticed for [WB/GCSM/1GD], which recorded the highest mechanical performance among all WB/GCSM composite systems.